LDL-C levels, lipid-lowering treatment and recurrent stroke in minor ischaemic stroke or TIA. Issue 4 (7th March 2022) - Pan, Yuesong; Wangqin, Runqi; Li, Hao; Jin, Aoming; Li, Jiejie; Lin, Jinxi; Meng, Xia; Xian, Ying; Laskowitz, Daniel T; Wang, Yongjun
Abstract : Background and purpose: Dyslipidaemia is a major risk factor for ischaemic stroke and transient ischaemic attack (TIA). This study aimed to investigate the association between baseline low-density lipoprotein cholesterol (LDL-C) level, lipid-lowering treatment and short-term risk of new stroke in patients with a minor ischaemic stroke or TIA. Methods: We derived data from the Clopidogrel in High-risk patients with Acute Non-disabling Cerebrovascular Events trial. Patients with a minor stroke or TIA were categorised by LDL-C level at baseline (<2.6 or ≥2.6 mmol/L (100 mg/dL)) and with or without lipid-lowering treatment after symptom onset. The primary outcome was a new ischaemic stroke at 3 months. The association of baseline LDL-C level, lowering treatment and outcomes were assessed. Results: Among 3027 patients, 2154 (71.2%) patients had an initial LDL-C ≥2.6 mmol/L, of which 1267 (41.9%) received lipid-lowering treatment. Elevated LDL-C level was associated with a higher risk of new ischaemic stroke at 3 months in patients without lipid-lowering treatment (adj.HR=1.35, 95% CI: 1.19 to 1.53), but not in those with lipid-lowering treatment (adj.HR=0.99, 95% CI: 0.82 to 1.19) (p for interaction=0.007). Patients with LDL-C ≥2.6 mmol/L had a numerically higher risk of ischaemic stroke (11.8% vs 8.0%, adj.HR=1.37, 95% CI: 0.96 to 1.96) in those without lipid-lowering treatment. For patients with LDL-C ≥2.6 mmol/L, lipid-lowering treatment was associated with reduced risk of ischaemic stroke at 3 months (7.9% vs 11.8%; adj.HR=0.54, 95% CI: 0.39 to 0.75). Conclusions: Elevated untreated baseline LDL-C level was associated with an increased short-term risk of ischaemic stroke among patients presenting with minor ischaemic stroke or TIA. There was potential benefit of lipid-lowering treatment in minor stroke or TIA patients with LDL-C ≥2.6 mmol/L. Trial registration number: NCT00979589 .